The Difference of Endometrial Vascular Endothelial Growth Factor (VEGF) Expression between Polycystic Ovarian Syndrome (PCOS) and Normal Women - Saputra, Ricky Bernadi; Budihastuti, Uki Retno; Sulistyowati, Sri; Melinawati, Eriana; Respati, Supriyadi Hari (Indonesian Journal of Medicine, 2020)
Background: Polycystic Ovarian Syndrome (PCOS) is an endocrine disorder in women characterized by increased levels of androgens, ovulatory dysfunction, and Polycystic Ovarian Morphology (PCOM), as well as a combination of classic clinical features. Women with PCOS experience changes in the endometrium and endometrial receptivity markers such as VEGF (Vascular Endothelial Growth Factor). VEGF increases the permeability and dilation of endometrial blood vessels which play an important role in implantation. This study aimed to analyze the difference of VEGF expression between women with PCOS and normal women.Subjects and Method: This study was a case-control study design conducted at the polyclinic of the Department of Obstetrics and Gynecology, Dr. Moewardi Hospital, Surakarta, Central Java, in July 2020. There were 30 infertile women with PCOS (diagnosis based on Rotterdam criteria, consensus 2003) and 30 women without PCOS as the sample of this study. The dependent variable was VEGF expression. The independent variables were age, BMI, family history with PCOS, menarche, occupation, and education. VEGF expression was obtained from an endometrial biopsy on days 19-24 of periods. The differences in VEGF expression (in %) were analyzed by the Mann-Whitney test. VEGF determinants were analyzed by a multiple linear regression.Results: The mean of VEGF expression in women with PCOS (Mean=64.33; SD=44.43) was higher than in women without PCOS (Mean= 7.90; SD=8.73) and the result was statistically significant (p<0.001). PCOS (b=42.09; 95%CI=64.26 to -19.93; p<0.001) and obese (b=38.63; 95%CI=-63.44 to -13.82; p=0.003) increased VEGF expression.Conclusion: VEGF expression in the endometrium of women with PCOS is higher than normal women.Keywords: VEGF, endometrium, Polycystic Ovarian SyndromeCorrespondence: Ricky Bernadi Saputra. Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Sebelas Maret/ Dr. Moewardi Hospital, Surakarta, Indonesia. Telp: 081221161933 Email: rickysaputradr@gmail.comIndonesian Journal of Medicine (2020), 05(03): 230-239https://doi.org/10.26911/theijmed.2020.05.03.08